Research results applied on small farms - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Cameroon's National Root Crops Improvement Programme (CNRCIP) has launched an extensive effort to apply the results of experiment station research on small farms. This is to be accomplished through researcher-managed verification trials of improved...